EXPLORING CAUSES OF WATER RESOURCE DEGRADATION (TOWARD THEORETICAL PERSPECTIVE AND ITS RELEVANCE TO EMPIRICAL CASES) - Rolia, Eva (Prodi Teknik Sipil Universitas Muhammadiyah Metro, 2012)
This paper tries to discuss water issue by exploring hydrologic cycle that can be understood as a whole phases undergone by water.